Kierkegaard's Catholic Reception and the Legacy of Vatican ii - Furnal, Joshua (Toronto journal of theology, 2016)
How can Søren Kierkegaard—a Protestant thinker from the nineteenth century, who was also a fierce critic of Christianity—be seen as an ally to contemporary Catholic theology? In this article, I argue that although he is not always recognized as such, Søren Kierkegaard has been an important ally for Catholic thinkers in the early twentieth century. Historically, some Catholic readers have been suspicious of Kierkegaard, viewing him as an irrational Protestant irreconcilably at odds with Catholic thought. Nevertheless, by surveying briefly a few important figures in the Catholic reception and engagement of Kierkegaard's writings across Europe in the early twentieth century, one begins to see how Kierkegaard's writings stimulated theological renewal that culminated in the achievement of the Second Vatican Council (1962-1965). In particular, this article highlights an unexpected yet important historical relationship between the European Catholic reception of Kierkegaard's writings by looking at important figures like Jean Daniélou, Yves Congar, Henri de Lubac, Hans Urs von Balthasar, and Cornelio Fabro who were associated with the ressourcement movement (1930-1960) leading up to Vatican ii.